Biosorption-Cum-Bioaccumulation of Heavy Metals from Industrial Effluent by Brown Algae: Deep Insight - Yadav P.; Singh J.; Mishra V. (My University, 2025)
Biosorption by marine brown algae is considered to be very effective as the brown algae is found in diverse size and are having better efficiency in removing the heavy metals form wastewater which is one of the most critical problem now a days. Many micro and macroalgae are responsible for the recovery of different heavy metals. The brown seaweeds have the highest sorption capacity or higher rate of bioaccumulation for heavy metal ion than that of red and green seaweeds. Marine algae are fast growing algae and can perform relatively better as it requires a small amount of nutrients, CO2 and sunlight for its survival. The present literature covers the biosorption by marine algae mainly the brown algae which can be used all around the year. The carboxyl acid group present in these biomass is found to be the most dominant as well as most abundant functional group that are followed by fucoidan. © Springer Nature Singapore Pte Ltd. 2019.